Conversion disorder and mass psychogenic illness in child neurology. (18th October 2013) - Mink, Jonathan W.
Abstract : A common problem faced by neurologists is the existence of disorders that present with neurological symptoms but do not have identifiable neurological bases. Conversion disorder is the most common of these disorders. In some situations, members of a cohesive social group will develop the same or similar symptoms. This review discusses conversion disorder in children, with an emphasis on function movement disorders. It also reviews a recent occurrence of mass psychogenic illness in New York State with discussion of the key features of mass psychogenic illness.